The Automation of Sound Absorption Coefficient Measurement - Denny Hermawanto; Achmad Suwandi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
By manual method, the sound absorption coefficient measurement should be done by utilizing many type of equipment such as: measuring amplifier, level recorder, band-pass filter, protactor, etc. However it caused inefficient and need longer time in processing measurement data, therefore the automation system of sound absorption coefficient has been realized. An acoustical real time analyzer type B&K 2144 has been used to record the decay of sound pressure level, thus the processing data is driven by computer software program. By using this developed measurement system, the configuration of equipment which is used in measurement system is becoming more simplified, moreover the time process which is required for sound absorption coefficient measurement can be reduced significantly.Keywords: sound absorption coefficient, automation measurement system